Dietary risk assessment in the WIC program : Committee on Dietary Risk Assessment in the WIC Program. (National Academy Press, 2002)
Contains an evaluation by the Committee on Dietary Risk Assessment in the WIC Program of the usefulness of assessing diet risk in determining eligibility of applicants for the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC).